Fons Iustitiae: Justice in the City of God - Boersma, Gerald P. (International journal of systematic theology, 2021)
This article seeks to account for the nature of human justice in the City of God. I argue that finite justice, for Augustine, is participatory; it always ‘refers’ itself to the font of justice from which it overflows; it is always received by participation in Christ’s justice. This claim implicates both of Augustine’s central adversaries in the City of God, namely, imperial paganism and Pelagianism. Attention to how Augustine weaves the two major polemical antagonists of the City of God, imperial paganism and Pelagianism, into the same cloth reveals a unified claim about justice in the City of God. Both of Augustine’s antagonists are guilty of claiming a self-referential and self-manufactured conception of justice. Pagans and Pelagians do not confess justice as a gift received; they instead treat it as something constructed on the tottering foundation of collective or personal virtue. Justice in both cases fails and finds its end in self-glorification and pride. Finally, I propose that Augustine’s participatory account of justice has implications for a vexed twentieth-century debate about the City of God, namely the question of what allegiance, responsibilities and loves citizens of the heavenly city ought to have towards the earthly city in which they live as pilgrims.